Livelihood sources in Climate-Smart Villages of Nyando Basin, Kenya: Findings from a climate-smart agriculture survey in Nyando Basin, Kenya - Njogu, Josephine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This brief summarizes findings of the research project “Using Climate-Smart Financial Diaries for Up-scaling in Nyando, Western Kenya”, a project led by the Amsterdam Center for World Food Studies (ACWFS) with participation of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in East Africa, the University of Nairobi’s School of Economics and Wageningen Economic Research. The findings are based on baseline data of an on-going bigger panel study involving 122 households located in the Climate-Smart Villages (CSVs) and a few non-CSVs in Nyando. The villages have similar characteristics in terms of climate, soils and main agricultural practices. They occupy the Nyando Basin and cut across Kisumu and Kericho counties. The project focus is assessing the financial inflows and outflows of households in these villages by gathering data on their income, consumption, savings, lending and investment patterns.